Luminescence chronology of Late Quaternary palaeo-lake deposits from the Upper Alaknanda Basin, Uttarakhand, India: Implication to palaeoclimate and depositional settings. (15th April 2022) - Pattanaik, Jitendra Kumar; Singh, Atul; Kumar, Haldhar; Singh Shah, Sunil; Semwal, Prabhat; Sujith Naik, M.; Nayak, Kalyani; Jaiswal, Manoj K.; Banerjee, Argha; Nainwal, Harish Chandra; Shankar, Ramachandran
Graphical abstract: Highlights: A paleo-lake deposit is reported from Upper Alaknanda Basin in the Badrinath Valley. OSL dating reveals 1st phase of sedimentation between 21.6 ± 4.7 to 10.5 ± 1.4 ka. Two phases of paleo-lake formation and outburst observed in the Badrinath Valley. Higher sedimentation characterise warm and wet periods (ca. 19 to 15 ka; 11 to 10 ka). Lower sedimentation rate, rhythmite and varve deposits correspond to a colder period (ca. 22 to 19 ka, and around 15 ka). Abstract: Lakes downstream of the glaciers receive glacial meltwater and sediment supply resulting in formation of thick succession of lacustrine deposits. In this work, we have identified one such palaeo-lake deposit in the Upper Alaknanda Basin, close to Badrinath town. The sediments are of lacustrine origin; however the continuity is broken by intermittent fluvial deposits, which indicate changes in the depositional environment. We used Optically Stimulated Luminescence (OSL) dating to develop a robust chronology of the palaeo-lake deposit. Grain size analyses of sediments were carried out to understand the depositional environment, and morphometric analysis of the valley was conducted to obtained clues about the neotectonic activities in the region. The OSL ages show that the deposition of the lake sediments occurred between 21.6 ± 4.7 ka to 10.5 ± 1.4 ka. Two phases of paleo-lake deposit and subsequent outburst is established from the OSL age, grain size distribution and on the basis of field observations. The high sedimentation rate in the upper part of the deposit indicates an increase in the monsoonal rainfall and glacial retreat post Younger Dryas event. The colder periods are represented by varves and rhythmites, while the warmer periods are represented by thick laminated sand. This study indicates that the glaciers in the Upper Alakanada Basin responded to the fluctuations in the palaeo-climate.